Electromagnetic properties and performance of exfoliated graphite (EG) – Thermoplastic polyurethane (TPU) nanocomposites at microwaves. (19th June 2015) - Valentini, M.; Piana, F.; Pionteck, J.; Lamastra, F.R.; Nanni, F.
Abstract: Nanocomposite materials based on commercial thermoplastic polyurethane (TPU) loaded with exfoliated graphite (EG) in concentration between 0 and 20 wt.% have been prepared with EG via melt mixing and compression molding. The materials' electromagnetic properties have been measured with wave-guide technique between 8.2 and 12.3 GHz. They had shown a clear proportional dependence of complex permittivity with EG content. Above 16 wt.% permittivity becomes frequency dependent. These results are discussed in view of material microstructure by means of scanning electron microscope (SEM) observations. Samples, with 20 wt.% EG and 4 mm thick, show an average value of −20 dB of shielding effectiveness (SE), which make them suitable as shielding material for commercial application. Simulations of metal backed configuration showed that important narrowband EM absorption (>−15 dB) can be achieved at 1 mm thickness, while multilayer structures are necessary to obtain EM broadband absorption (>−10 dB between 8.5 and 12 GHz) can be achieved in 6 mm thick samples.